Country Equity: an empirical investigation of the image of brazilian and chisene footwear among chilean consumers - Anita Fernandes Koenigsdorf; Angela da Rocha; Jorge Ferreira da Silva (Internext: Revista Eletrônica de Negócios Internacionais, 2014)
Based on the concept of country equity, which has been adapted from the construct of brand equity to the specific case of country brands, this study aimed at empirically investigating the influence of country equity on the attitudes of foreign consumers towards a specific product category. The model developed by Pappu and Quester (2010), formed by five dimensions (country awareness, macro country image, micro country image, perceived quality and country loyalty) was combined with affective indicators from Häubl (1996). The proposed model was tested in a non durable products category, footwear. Results did not support the proposed dimensions